Therapeutic Enzyme-Responsive Nanoparticles for Targeted Delivery and Accumulation in Tumors - Callmann, Cassandra E.; Barback, Christopher V.; Thompson, Matthew P.; Hall, David J.; Mattrey, Robert F.; Gianneschi, Nathan C. (Advanced materials (Weinheim), 2015)
An enzyme‐responsive, paclitaxel‐loaded nanoparticle is described and assessed in vivo in a human fibrosarcoma murine xenograft. This work represents a proof‐of‐concept study demonstrating the utility of enzyme‐responsive nanoscale drug carriers capable of targeted accumulation and retention in tumor tissue in response to overexpressed endogenous enzymes.